The effect of temperature on the dispersion of α-Mangostin in PNIPAM microgel system / Madihah Ahmad, Bohari M. Yamin and Azwan Mat Lazim - Ahmad, Madihah; M. Yamin, Bohari; Mat Lazim, Azwan (Research Management Institute, 2012)
α-Mangostin was extracted from the pericarp of the Malaysian local Garcinia mangostana linn., The structure was characterised by Infrared red, UV-Visible and Nuclear Magnetic Resonance spectroscopic data. The fluorescence peak at 500nm in ethanol was not observed in PNIPAM microgel solution. The increase of colloidal size of the gel in the presence of α-mangostin was studied by Dynamic Light Scattering and Transmission Electron Microscope. The size of the particle also increases with increasing temperature up to 45⁰C after which it began to shrink. The TEM micrograph at 45°C showed a uniformly structured pattern of the gel occurs in the range of the lowest solution critical temperature